Differentiating Exponential functions In Exercise,find the derivative of the function. See Example 2 and 3.
f(x) = (e^x + e^-x)4/2

Respuesta :

Answer: The derivative would be [tex]f'(x)=2(e^{2x}-e^{-2x})[/tex]

Step-by-step explanation:

Since we have given that

[tex]f(x)=(e^x+e^{-x})^{\frac{4}{2}}\\\\f(x)=(e^x+e^{-x})^2[/tex]

As we will use "Chain Rule"

and at last we will use the identity ''[tex]a^2-b^2=(a-b)(a+b)[/tex]''

We need to find the derivative of the function:

[tex]f'(x)=2(e^x+e^{-x})(e^x-e^{-x})\\\\f'(x)=2(e^{2x}-e^{-2x})[/tex]

Hence, the derivative would be

[tex]f'(x)=2(e^{2x}-e^{-2x})[/tex]